Primary School in the Time of Covid-19: Parents’ Engagement in Students’ Online Learning - Desy Mutia Sari; Agus Widyantoro; Sonia Octavia (Universitas Pendidikan Ganesha, 2021)
This study aims to gather data from public and private primary school parents located in the urban, suburban, and rural areas that would contribute to understanding parental roles regarding fully online learning for their children during COVID-19. We also discussed several parents’ self-identified issues on their ability to participate in their children’s fully online learning experiences. A qualitative study was employed as the methodological basis for eliciting 12 parents whose children in 3rd, 4th, and 5th-grade attending conventional learning before school closure due to the pandemic. The semi-structured interview was conducted, and verbatim transcripts were analyzed using inductive and thematic analysis approaches. Four major themes were identified from parents’ role during home learning, including organizing and managing, mentoring and instructing, facilitating, and motivating children learning. Online learning relied on how active parents engage and maintain children’s interaction with learning content, teachers, and peers to familiarise their children with online educational settings successfully. However, personal issues arise, which can be stressful as teaching young learners virtually need special attention. Having significant responsibilities to their children learning, parents disclosed key issues and struggled, resulting in a rapid move from face-to-face to online instructions; learning value, learning efficiency, mental and physical health, accessibility.